Effect Of Fiber Surface Treatment On Mechanical And Thermal Properties Of Polylactic Acid-Kenaf Fiber Composite - Chai, Poi Seng (Universiti Sains Malaysia, 2017)
In the present study, the effect of fiber surface treatment on mechanical and thermal properties of Polylactic acid/kenaf fiber composite manufactured by single screw extruder followed by injection moulding were investigated. The alkali treatment was done by treating the kenaf fiber with 5 % NaOH solution for 2 h while silane treatment was done by soaking fiber in 5 wt% of silane coupling agent which was dissolved in a mixture of water – ethanol (40:60 w/w) for 3 h. The influence of fiber treatment on chemical and morphological properties of kenaf fiber was investigated with Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). It was found that alkali treatment effectively removed surface impurities and non-cellulosic materials such as hemicellulose and lignin while silane treatment did not show a significant effect on these properties. Mechanical properties of PLA/kenaf fiber composite were investigated with tensile and impact test, while the thermal properties measurement was carried out using Thermogravimetric Analysis (TGA), and Differential Scanning Calorimetry (DSC). The alkali treatment was found to improve both mechanical and thermal properties of PLA/kenaf fiber composite as compared to untreated fiber composite which appears to be due to the removal of hemicellulose and lignin roughen the fiber surface, led to increase in interfacial adhesion via mechanical interlocking. The mechanical and thermal properties of silane treated fiber composite were increased further due to enhanced interfacial adhesion by chemical bonding which is stronger than mechanical interlocking.